Training design and delivery - McArdle, Geri E. H. (ASTD Press, 2007)
Trainers are always on the lookout for a quick, easy-to-use guide to help them through the process of designing, producing, implementing, delivering, and evaluating training programs. Training Design & Delivery is intended to be that simple, single-source guide for every trainer, training manager, and even the occasional trainer.